Parapharyngeal Neurofibroma Originating From The Vagus Nerve In A Patient With Von Recklinghausen′s Disease - Das Nillay Kanti; Mishra Saibal; Saha Somnath (Wolters Kluwer Medknow Publications, 2004)
A case of unilateral parapharyngeal neurofibroma occurring in a 25 year old female with von Recklinghausenâ€s disease is discussed in this report because of the rarity of such a condition. Parapharyngeal neurofibroma usually arises from the vagus nerve and very rarely they are associated with von Recklinghausenâ€s disease or Neurofibroamatosis type 1. It typically presents with a longâ€"standing history of throat/neck mass with/without neurological deficit. CT scan reveals a moderately enhancing mass, occasionally with central necrosis or cavitations. This, together with spindle shaped cells seen on aspiration cytology, if done, strongly suggests a neurofibroma and excision of the tumor is the treatment of choice. In this patient no sign of malignancy was detected and the two year followâ€"up period was uneventful.